Stress Coping Strategies in Parents of Children With Autism Spectrum Disorder - Kalalo, Royke Tony; Setiawati, Yunias (International Journal of Psychosocial Rehabilitation, 2020)
Autism spectrum disorder is a neurodevelopmental disorder and can be a lifelong disorder. From the moment a diagnosis of autism is revealed, parents are obliged to take an important role and caring for children with autism spectrum disorder often presents challenges related to stress that parents can experience. Changes in behavior in one family member than will give effect to other family members. At present, in handling autism spectrum disorder, other than through interventions that are focused on stimulation of development and reduction of maladaptive behaviors, the other main consensus is to help families achieve appropriate care, obtain appropriate coping mechanisms and reduce stress on parents or caregivers. There are several measuring instruments that are often used to help clinicians determine the degree of stress in parents who have children with autism spectrum disorder including Parent Stress Index (PSI), Parental Stress Scale (PSS), and Autism Parenting Stress Index (APSI). Some strategies in dealing with stress in family especially parents of children with autism spectrum disorder are parental psychoeducation strategy, parent training strategy, useful parenting coping strategies, parents self care strategy, eco-map strategy, group therapy strategies, individual therapy for parents and social support strategy.